Comparison of mercury and zinc profiles in peat and lake sediment archives with historical changes in emissions from the Flin Flon metal smelter, Manitoba, Canada - Outridge, P. M.; Rausch, Nicole; Percival, J. B.; Shotyk, William; McNeely, R. (The science of the total environment, 2011)
The copper-zinc smelter at Flin Flon, Manitoba, was historically the largest single Hg point-source in Canada, as well as a major source of Zn. Although emissions were reported by industry to have declined significantly since the late 1980s, these reductions have never been independently verified. Here, the histories of Hg and Zn deposition over the past century or more were determined at five lake sediment and three peat study sites in the surrounding region. At sites spanning the range from heavy to minor pollution, lake sediment Hg and Zn concentration and flux profiles increased significantly in the early 1930s after the smelter opened. Two of the three peat archives were wholly or partially compromised by either physical disturbances or biogeochemical transitions which reduced their effectiveness as atmospheric metal deposition recorders. But the remaining peat records, including a detailed recent 20yr record at a moderately polluted site, appeared to show that substantive reductions in metal levels had occurred after the late 1980s, coincident with the reported emission reductions. However, the lake sediment results, taken at face value, contradicted the peat results in that no major declines in metal concentrations or fluxes occurred over recent decades. Mercury and Zn fluxes have in fact increased substantially since 1988 in most lakes. We suggest that this discrepancy may be explained by catchment soil saturation by historically deposited metals which are now mobilizing and leaching into lakes, as has been reported from other smelter polluted systems in Canada, whereas the upper sections of the peat cores reflected recent declines in atmospheric deposition. However, further research including instrumented wet and dry deposition measurements and catchment/lake mass balance studies is recommended to test this hypothesis, and to provide definitive data on current atmospheric metal deposition rates in the area.
Erstmals online veröffentlicht am 20. November 2010
Gesehen am 19.10.2022